An assessment of injection site reaction and injection site pain of 1‐month and 3‐month long‐acting injectable formulations of paliperidone palmitate. Issue 4 (14th February 2018) - Kern Sliwa, Jennifer; Savitz, Adam; Nuamah, Isaac; Mathews, Maju; Gopal, Srihari; Elefant, Erica; Najarian, Dean; Alphs, Larry
Abstract: Purpose: To evaluate injection site reactions and pain following paliperidone palmitate 1‐month (PP1M) and 3‐month (PP3M) administration using safety data of double‐blind (DB), noninferiority study. Methods: Patients ( n  = 1, 429) with schizophrenia, treated with PP1M (50–150 mg‐eq, 17‐week open‐label [OL] phase) were randomized to PP1M or PP3M in 48‐week DB phase. Findings: PP1M and PP3M injections were well tolerated. Incidence of induration, redness, and swelling were low in both phases (OL: 9–12%; DB: 7–13%), and were mostly mild in both groups. Mean ( SD ) visual analog scale scores decreased from OL‐baseline (22.0 [21.6]) to DB‐baseline (19.5 [20.6] vs. 18.4 [20.4]) and DB‐endpoint (15.6 [17.9] vs. 15.5 [18.3]). Practice Implications: Injection site reactions and pain were low and similar between both treatments, regardless of administration site and dose.